Immune microenvironment infiltration landscape and immune-related subtypes in prostate cancer - Wu, Wei; Wang, Xin’an; Le, Wei; Lu, Chang; Li, Haopeng; Zhu, Yaru; Chen, Xi; An, Wenbin; Xu, Chengdang; Wu, Qiang; Wang, Licheng (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) primary composes of cancer cell, cancer-infiltrating immune cells and stroma cells. Tumor cells affect TME by releasing cellular signaling molecules to induce immune tolerance. TME-related immune cell infiltration (ICI) significantly influences multiple cancers outcomes. But immune-related ICI model of TME in prostate cancer (PC) has not yet been expounded so far. Hence that, three ICI clusters were defined based on TME immune cells infiltration model of 1,099 prostate cancer (PC) by employing CIBERSORT and ESTIMATE algorithms. We subsequently identified three distinct ICI gene clusters on ground of overlapped differential expression genes (DEGs) within ICI clusters. Additionally, the ICI scores were calculated by principal-component analysis (PCA). According to results, elevated ICI score patients have worse prognosis as well as reduced transcriptional level of immune-checkpoint genes and immune-activity genes. Furthermore, subtypes with raised ICI score enriched in TGF-β and WNT pathways, which suggesting T lymphocyte repression may be accompanied with worse prognosis. Moreover, the ICI score was positively correlated to tumor mutation burden (TMB) value in prostate cancer. Patients with lower ICI score shown clinical benefit and immunotherapy advantages, indicating ICI score shows an accurate and efficient predictor to assessing effect of immunotherapy response. Overall, our study exhibited a comprehensive immune-related ICI landscape of prostate cancer, and it may supply guidance for the current immunotherapy strategy research for prostate cancer.